Making disability rights real in Southeast Asia : implementing the UN Convention on the Rights of Persons with Disabilities in ASEAN - Cogburn, Derrick L.; Kempin Reuter, Tina, 1976- (Lexington Books, 2017)
"The implementation of the first human rights and development treaty of the twenty-first century in Southeast Asia has global impact. This book explores the Convention on the Rights of Persons with Disabilities implementation in all ten countries of ASEAN, and is a resource to development, human rights, and disability scholars around the world"--